2000
DOI: 10.1093/jexbot/51.343.197
|View full text |Cite
|
Sign up to set email alerts
|

ABA activation of an MBP kinase in Pisum sativum epidermal peels correlates with stomatal responses to ABA

Abstract: In-gel protein kinase assays using myelin basic protein (MBP) as substrate have been used to demonstrate that abscisic acid (ABA) activates an MBP kinase (AMBP kinase) in epidermal peels prepared from leaves of the Argenteum mutant of pea, Pisum sativum L. AMBP kinase has the characteristics of a mitogen-activated protein kinase (MAPK): it utilizes MBP preferentially as an artificial substrate, it is rapidly and transiently activated, it is of the appropriate size (molecular weight c. 45 kDa), requires tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 23 publications
0
73
0
1
Order By: Relevance
“…Thus, NtMPK4 might function at early stages of ROS signaling by controlling the entrance gate for ozone uptake from the environment. A MAPK that is activated by ABA was also identified in pea (Pisum sativum) guard cells (Burnett et al, 2000), providing further evidence for a role of MAPKs in stomatal control. MAPK modules do not only affect the aperture but also the density of stomata.…”
Section: Ros and Stomatamentioning
confidence: 81%
“…Thus, NtMPK4 might function at early stages of ROS signaling by controlling the entrance gate for ozone uptake from the environment. A MAPK that is activated by ABA was also identified in pea (Pisum sativum) guard cells (Burnett et al, 2000), providing further evidence for a role of MAPKs in stomatal control. MAPK modules do not only affect the aperture but also the density of stomata.…”
Section: Ros and Stomatamentioning
confidence: 81%
“…ABA may enhance either expression (Hwang and Goodman, 1995;Hong et al, 1997;Lee et al, 1998;Mikami et al, 1998;GomezCadenas et al, 1999;Piao et al, 1999) or activity (Li and Assmann, 1996;Burnett et al, 2000) of these kinases. Although initial functional studies with pharmacological inhibitors did not discriminate among the roles of individual family members, recent studies with dominant negative alleles have assayed the role of specific kinases (Sheen, 1996;Li et al, 2000).…”
Section: Components Of Early Steps In Aba Signal Transductionmentioning
confidence: 99%
“…Furthermore, a study with pea epidermal peels showed that the MAPKK inhibitor PD98059 inhibits ABA-induced stomatal closure and expression of an ABA-inducible dehydrin gene (16,17). Despite these studies indicating that MAPK cascades function in ABA signaling, it remains to be established which specific MAPKs, MAPKKs, and MAPKK kinases (MAPKKKs) form a complete cascade to mediate ABA signaling in guard cells.…”
mentioning
confidence: 99%